Hazard assessment of quinaldine-, alkylcarbazole-, benzene- and toluene-based liquid organic hydrogen carrier (LOHCs) systems. Issue 1 (19th December 2018) - Markiewicz, Marta; Zhang, Ya-Qi; Empl, Michael T.; Lykaki, Marianna; Thöming, Jorg; Steinberg, Pablo; Stolte, Stefan
Abstract : Proactive, comparative environmental hazard assessment of LOHC systems based on alkylcarbazoles, quinaldine, benzene and toluene including H2 -rich, H2 -lean and partially hydrogenated forms. Abstract : Due to the finite nature and scarcity of crude oil-based fuels, increasing attention is being directed towards various forms of renewable energy. To obtain a fully functional renewable energy system, some compensation for the spatiotemporal fluctuations in renewable energy sources is necessary. In this context, the so-called liquid organic hydrogen carrier (LOHC) systems are promising from a technological perspective, although their impact on the environment and on animal/human health has not been considered in great detail. Hence, we present a proactive, comparative environmental hazard assessment of LOHC systems based on three alkylcarbazoles and quinaldine, including H2 -rich, H2 -lean and intermediate ( i.e., partially hydrogenated) forms as well as on benzene and toluene, also including H2 -rich forms (cyclohexane and methylcyclohexane, respectively). Specifically, the present study reports on the enzyme inhibitory (acetylcholinesterase), mutagenic (Ames test) and cytotoxic (IPC-81 cell line) activities of the above-mentioned compounds. Furthermore, the aquatic toxicity of the test compounds to marine bacteria ( Vibrio fischeri ), green algae ( Raphidocelis subcapitata ), aquatic plants ( Lemna minor ) and water fleas ( Daphnia magna ) was assessed in addition to their biodegradability, using inocula from a wastewater treatment plant. To complete the picture, we compared the effects of the LOHCs investigated herein with those of diesel oil. In this context, our results suggest that the quinaldine-based LOHC system is comparable with diesel oil in terms of ecotoxicity but is less biodegradable. The alkylcarbazoles appear to be more toxic and poorly biodegradable. Lastly, the benzene and toluene-based LOHC systems give serious reasons for concern in terms of human and aquatic toxicity. Nevertheless, due to their less complex composition, the assessment of the LOHC systems carries much lower levels of uncertainty regarding adverse effects. Additionally, because of more favourable physicochemical properties ( e.g., higher boiling points), some LOHCs are safer for handling and transportation. Finally, the possibility of storing and using renewable energy offers a significant environmental and economic benefit.